Pengaruh Transformasi Digital Dan Beban Kerja Terhadap Kinerja Pegawai Badan Pertanahan Nasional Kabupaten Ogan Komering Ul Sumatera Selatan - Dhea Kharisma Putri; Mohammad Kurniawan DP; Yeni Yeni (Management Studies and Entrepreneurship Journal (MSEJ), 2026)
This study aims to analyze the effect of Digital Transformation and Workload on Employee Performance at the National Land Agency (Badan Pertanahan Nasional) of Ogan Komering Ulu Regency, South Sumatra, using a quantitative approach with a sample of 74 respondents. Data were collected through questionnaires and analyzed using multiple linear regression with the assistance of SPSS version 27. The results indicate that partially, the Digital Transformation variable has a positive and significant effect on Employee Performance, with a t-value of 5.337 > t-table of 1.99 and a significance value of 0.000 < 0.05. Meanwhile, the Workload variable also has a positive and significant effect on Employee Performance, with a t-value of 5.321 > t-table of 1.99 and a significance value of 0.000 < 0.05. Simultaneously, Digital Transformation and Workload have a positive and significant effect on Employee Performance, with an F-value of 236.802 > F-table of 3.12 and a significance value of 0.000 < 0.05. The correlation coefficient (R) is 0.933 and the coefficient of determination (R²) is 0.870, indicating that both variables are able to explain 87.0% of the variation in Employee Performance, while the remaining 13.0% is influenced by other variables not examined in this study.